2012
DOI: 10.1007/s00428-012-1343-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear, but not cytoplasmic, localization of survivin as a negative prognostic factor for survival in upper urinary tract urothelial carcinoma

Abstract: Survivin, a member of the inhibitor of apoptosis protein gene family, inhibits apoptosis and promotes mitosis. We determined whether nuclear or cytoplasmic localization of survivin could predict survival of patients with upper urinary tract urothelial carcinoma (UUTUC). Immunohistochemical staining for survivin was carried out on archival specimens from 125 consecutive patients with UUTUC who underwent radical nephroureterectomy. Nuclear and cytoplasmic staining of survivin was scored and compared with clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Because our B16 tumors (H-2 b ) lacked the relevant restriction element (H-2 d ) for recognition by the CL4 TCR, we could rule out direct presentation of the antigen by the tumors [33] or by MHC-peptide exchange; a phenomenon described as “cross dressing” [20]. Thus in tumor-bearing C57BL/6 x BALB/C F 1 mice (H-2 bxd ), the proliferation of adoptively transferred H-2 d restricted CL4-TCR transgenic CD8 T cells could only be induced when F1 host APCs cross-present CL4 antigen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because our B16 tumors (H-2 b ) lacked the relevant restriction element (H-2 d ) for recognition by the CL4 TCR, we could rule out direct presentation of the antigen by the tumors [33] or by MHC-peptide exchange; a phenomenon described as “cross dressing” [20]. Thus in tumor-bearing C57BL/6 x BALB/C F 1 mice (H-2 bxd ), the proliferation of adoptively transferred H-2 d restricted CL4-TCR transgenic CD8 T cells could only be induced when F1 host APCs cross-present CL4 antigen.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the tumor-associated antigen (TAAs) currently targeted in anti-tumor immunotherapy, such as survivin, MAGE-A10, and WT1, are predominantly expressed in the nucleus [12][14]. Moreover, several clinical studies have correlated the nuclear localization of different TAAs with poor clinical outcome in a variety of cancer types [15][20]. Therefore, it is important to understand the relative availability for cross-presentation of antigens in the nuclear compartment compared to other cellular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some immunohistochemistry (IHC) studies reported survivin expression in a high proportion of UC patients [18, 19]. In another study, survivin expression was observed in tumor cells, but not in normal urothelial cells, in patients with superficial bladder cancer [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear localization such as we observed in ACP is described to be a negative prognostic factor in non-small cell lung cancer, 20 laryngeal cancer, 43 and urothelial carcinoma, 34 where it was associated with invasion, progression, and worse prognosis as well as higher recurrence rates. In contrast, colon carcinoma demonstrated better outcome if survivin was present in the nucleus.…”
mentioning
confidence: 51%